STUDI PARTAI DEMOKRAT PADA PILKADA 2005 DI KABUPATEN REMBANG - Sulistyawati, Dyah Ayu (Candi)
The aims of this research is to describe : (1) History first of build Partai Demokrat and structure organization of Partai Demokrat at Rembang Regency. (2) Process and result of local elections 2005 at Rembang Regency. (3) Strategic of winning local elections 2005 at Rembang Regency. This researchs method is historical method with heuristic, criticism, interpretation, and historiography. Source of data used in this research are primary sources and secondary sources. Collecting data by interview, observation and literature study. The data analysis technique used is the technique of historical analysis, by performing external and internal criticism. Based on these result it can be conclude : (1) History first of build Partai Demokrat and structure organization of Partai Demokrat at Rembang Regency are prepare for elections president and vice president 2004 in directly. Building of DPC Partai Demokrat at Rembang Regency while to local electing and it can be early change political system centralistic to be decentralistic. (2) Process and result of local elections 2005 at Rembang Regency are winning of company regent that be candidate by Partai Demokrat in the manner of 50 % voters. Because of combine between entrepreneur and religionist be a prime power to get support from Rembang Regency?s people. (3) Strategic of winning local elections 2005 at Rembang Regency are make a election group that prepare, result, and last result to local election. And coordinate in village level for more be collect an aspiration and necessaries of Rembang Regency?s people in common. In addition also make even programs that need and suitable of  Rembang Regency?s people.